Pharmacology and phytochemistry studies in Peltophorum africanum - Ofentse Mazimba (Bulletin of Faculty of Pharmacy Cairo University, 2014)
Peltophorum africanum Sond is an ethnomedicinal plant in the family Fabaceae. This literature report captures information about the ethnomedical uses, pharmacology and phytochemistry of P. africanum within the last four decades. The literature surveyed revealed the presence of different types of polyphenols whose content was higher in the bark and roots than the leaves. The plant polar extracts are rich in phenolic compounds and shows high antioxidant properties. The root and stem extracts are active against bacteria, parasites and HIV. There were no reports on the quality control of P. africanum as a herbal drug, nor a systematic identification of which phytochemicals are responsible for most of the pharmacological activities. Betulinic acid found in the bark is a known anti HIV agent. The reports on the pharmacological functions and the phytochemical studies which were started based on the traditional uses and botanical information justify the ethnomedicinal uses of the tree.